Combined effect of steel slag as a partially replaced material for coarse aggregates and water-cement ratio on the chloride resistance of concrete / Fauzi ... [et al.] - Fauzi, M.A; Rosseli, S.R; Hasbul, J.; Ridzuan, A. R. M. (2016)
Test was carried out to study the effect of the utilisation of steel slag (SS) as a coarse aggregate for concrete work to assess the chloride resistant in Concrete. Seventy-two (72) specimens were prepared with three water-cement ratios (0.58, 0.64 and 0.70). For each series of water-cement ratio twenty-four (24) specimens were prepared for each series, and concrete was designed with various amount of aggregate proportion with Natural aggregate (NA) and steel slag (10%, 50%, and 100%). The size of specimens used was 150 mm diameter x 60 mm height and 1M sodium chloride (NaCl) solution was prepared for 90-days immersion test. Weight change, dimension changed and depth of chloride penetration were monitored throughout the duration period. Effect of steel slag aggregate and water-cement ratio (w/c) proportion on chloride resistant are presented and analysed. There is no significant change in weight and dimension with respect to SS replacement was found. Specimens with 100% SS have a lower chloride depth penetration compared to concrete those made of 100% NA, 10% SS, and 50% SS. The value of weight change decreased with increasing w/c, but the optimal effect on the dimension and chloride penetration increased with increasing w/c for all mixes.